Systematic observation as a tool for analyzing the motivational climate in physical education - J. A. Julián; A. Abarca-Sos; A. Aibar; C. Peiró-Velert; E. Generelo (Asociación Española de Ciencias del Deporte, 2010)
This article describes an instrument designed for systematic observation and identifies strategies and variables associated with learning-oriented motivational climates (or task-involving) created by physical education teachers. It also aims to verify compliance with teachers' behaviours during the implementation of a teaching unit focused on long-distance running to promote active lifestyles. This is to say, that teachers participating in a training program meet the educational guidelines appropriate to develop an adaptive motivational climate in their classrooms. The instrument for climate analysis through systematic observation is based on the six areas of TARGET (Ames, 1992 and Epstein, 1988) and includes the key guidelines established by Generelo, Julian and Zaragoza (2009) to create a learning-oriented climate in physical education lessons. Key Words: teaching skills, TARGET, systematic observation, motivational climate, physical education